Nasolabial Cyst: Our Experience and Review of Literature - Abhay kr.Singh; Shruti Tandon; Tarun Malhotra; Sushil Gaur; Abhinav Raj (Journal of Coastal Life Medicine, 2022)
Nasolabial cyst is a rare non odontogenic development cyst in maxillofacial area. They present as painless unilateral swelling in the nasal alar area. The lesion is submucosal and extraosseous and it expands via the gingivobuccal sulcus. This paper presents a case series of 5 patients in a tertiary care hospital in Ghaziabad , in light of previous literature. Clinical suspicion and examination is the main diagnostic modality. Complete surgical excision is the main treatment modality. We emphasise on aspiration of fluid before sharp dissection at nasal floor to prevent accidental spillage of cyst fluid and to ensure complete excision due to better visualization.